Mouthguards: does the indigenous microbiome play a role in maintaining oral health? - Kumar, Purnima S.; Mason, Matthew R. (Frontiers in Cellular and Infection Microbiology, 2015)
The existence of symbiotic relationships between bacteria in different ecosystems and their host niches have long been known to science. The human body also hosts vast numbers of bacteria in several habitats. Emerging evidence from the gastro-intestinal tract, genito-urinary tract and respiratory indicates that there are several health benefits to hosting a complex and diverse microbial community i. Bacteria colonize the oral cavity within a few minutes after birth and form stable communities . Our knowledge of the oral microbiome has expanded exponentially with development of novel exploratory methods that allow us to examine diversity, structure, function and topography without the need to cultivate the individual components of the biofilm. The purpose of this perspective, therefore, is to examine the strength of current evidence supporting a role for the oral microbiome in maintaining oral health. While several lines of evidence are emerging to suggest that indigenous oral microbiota may have a role in immune education and preventing pathogen expansion, much more work is needed to definitively establish whether oral bacteria do indeed contribute to sustaining oral health, and if so, the mechanisms underlying this role.